Active tourism in the community. Relationship between perceived impacts on residents and support for sector development - González-García, R. J.; González-Serrano, M. H.; Ayora-Pérez, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The relationship between the tourism sector and sport has grown in importance, both academically and professionally. Residents also have an important role to play in harmonizing the development of the activity in the community, especially in those towns where tourism is the predominant sector. The objective of this study is to analyse which impacts associated with active tourism are perceived by residents and which are the best predictors of support for the development of this type of activity in the community. In addition, a descriptive analysis of the items corresponding to residents’ perceptions of the impacts associated with active tourism has been carried out, as well as their support for its development in the area. Consequently, the importance of the assessment of these impacts by the bodies responsible for planning, organising and managing the sector is significant.